Prevalence of diabetes in Australia: insights from the Fremantle Diabetes Study Phase II. Issue 7 (8th July 2018) - Davis, Wendy A.; Peters, Kirsten E.; Makepeace, Ashley; Griffiths, Shaye; Bundell, Christine; Grant, Struan F. A.; Ellard, Sian; Hattersley, Andrew T.; Paul Chubb, Stephen A.; Bruce, David G.; Davis, Timothy M. E.
Abstract: Background: Accurate diabetes prevalence estimates are important for health service planning and prioritisation. Available data have limitations, suggesting that the contemporary burden of diabetes in Australia is best assessed from multiple sources. Aims: To use systematic active detection of diabetes cases in a postcode‐defined urban area through the Fremantle Diabetes Study Phase II (FDS2) to complement other epidemiological and survey data in estimating the national prevalence of diabetes and its types. Methods: People with known diabetes in a population of 157 000 were identified ( n = 4639) from a variety of sources and those providing informed consent ( n = 1668 or 36%) were recruited to the FDS2 between 2008 and 2011. All FDS2 participants were assigned a type of diabetes based on clinical and laboratory (including serological and genetic) features. Data from people identified through the FDS2 were used to complement Australian Health Survey and National Diabetes Services Scheme prevalence estimates (the proportions of people well controlled on no pharmacotherapy and registering with the National Diabetes Services Scheme respectively) in combination with Australian Bureau of Statistics data to generate the prevalence of diabetes in Australia. Results: Based on data from multiple sources, 4.8% or 1.1 million Australians had diabetes in 2011–2012, of whom 85.8% had type 2 diabetes, 7.9% type 1 diabetes and 6.3% other types (latent autoimmune diabetes of adults, monogenic diabetes and secondary diabetes). Conclusions: Approximately 1 in 20 Australians has diabetes. Although most have type 2 diabetes, one in seven has other types that may require more specialised diagnosis and/or management.